Pengaruh Dana Pihak Ketiga, Kecukupan Modal Dan Suku Bunga Kredit Terhadap Return On Assets (ROA) BANK (Studi Kasus Pada Bank Persero Periode 2020-2023) - Rita Lestari; Amas Priatna, Isep (Universitas Islam Negeri Raden Intan Lampung, 2025)
This research aims to determine the influence of Third Party Funds, Capital Adequacy Ratio, and Credit Interest Rates on Return On Assets in Persero Banking Companies for the 2020-2023 period. The research method used in this research is a quantitative research method. The population used is the financial reports of PT Bank Mandiri (Persero) Tbk, PT Bank Rakyat Indonesia (Persero) Tbk, PT Bank Tabungan Negara (Persero) Tbk, and PT Bank Negara Indonesia (Persero) Tbk from the 2020-2023 quarterly period. The data analysis used is Panel Data Regression analysis using Eviews 12. The results of the t test (partial) obtained that Third Party Funds partially have an effect on Return On Assets (ROA), Capital Adequacy Ratio (CAR) partially has a significant effect on Return On Assets (ROA). Interest Rates partially have a significant effect on Return On Assets (ROA. The results of the F test (simultaneous), DPK, CAR and Interest Rates have a significant effect on Return On Assets (ROA). This is also reinforced by the results of the Fcount value (30.22457) > Ftable (2.76) and a significance value of 0.000.